(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The check-list of Shazkyy national natural park lakes diatoms is presented. It consists of 284 species (298 including infraspecific taxa), 29 of which is new for the territory of Ukraine and 219 for the Shazkyy national natural park lakes.